2011
DOI: 10.2202/1544-6115.1604
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Past Treatments and Their Outcome Improves Prediction of In Vivo Response to Anti-HIV Therapy

Abstract: Infections with the human immunodeficiency virus type 1 (HIV-1) are treated with combinations of drugs. Unfortunately, HIV responds to the treatment by developing resistance mutations. Consequently, the genome of the viral target proteins is sequenced and inspected for resistance mutations as part of routine diagnostic procedures for ensuring an effective treatment. For predicting response to a combination therapy, currently available computer-based methods rely on the genotype of the virus and the composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… Saigo et al (2011) investigated the association between sequences of antiviral pharmacological treatment/virus genotype changes and the occurrence of treatment failure. The data source was the EuResist integrated database which contains the treatment history (e.g., 61,831 different pharmacological treatments) of 18,467 patients with HIV from four different countries (e.g., Germany, Italy, Luxembourg, and Sweden) collected in the period 1987–2007.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Saigo et al (2011) investigated the association between sequences of antiviral pharmacological treatment/virus genotype changes and the occurrence of treatment failure. The data source was the EuResist integrated database which contains the treatment history (e.g., 61,831 different pharmacological treatments) of 18,467 patients with HIV from four different countries (e.g., Germany, Italy, Luxembourg, and Sweden) collected in the period 1987–2007.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that LASSO (mean of the results obtained with the three different datasets—AUC: 0.83; SD: 0.02) and the support vector machine (AUC: 0.79; SD: 0.02) had a higher value of AUC than logistic regression (AUC: 0.77; SD: 0.07). The authors emphasized the LASSO exerted its best performance especially for patients with many treatment changes (≥ 10) ( Saigo et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…3) Ravanelli et al used a LASSO regression to assess the predictive value of computed tomography texture analysis on survival in patients with lung adenocarcinoma treated with tyrosine kinase inhibitors (Ravanelli et al, 2018). 4) Saigo et al used a LASSO regression to assess if the history of medical treatments predict anti-HIV therapy response (Saigo et al, 2011).…”
Section: Ridge Elasticnet and Lassomentioning
confidence: 99%
“…In addition to controlled clinical trials, analyzing data from large observational cohort studies is a promising way to identify predictors of treatment outcome, even if the availability of drugs and therapeutic strategies change over time [3]. This approach can be based on modeling the risk of acquiring additional mutations [4], on estimating future drug options [5], on predicting the time to virological failure [6], [7], or on classifying the regimens of treatment change episodes (TCEs) as successful versus failing, depending on the patient's response to therapy.…”
Section: Introductionmentioning
confidence: 99%